Effect of plant extracts on the growth of Microsporum gypseum - Sowjanya, N C; Manohara Chary, C (Journal of Phytology, 2012)
The aqueous extracts at two different concentrations (5% and 10%) of Azadirachta indica, Lawsonia inermis, Allium sativum, Murraya koenigii, Ocimum sanctum were used to test their antifungal properties against the keratinophilic fungus Microsporum gypseum The present study revealed that Allium sativum and Ocimum sanctum at 10% conc. were more pronounced compared to all the other extracts followed by Azadirachta indica, Lawsonia inermis and Murraya koenigii.